1991
DOI: 10.1002/jlac.199119910115
|View full text |Cite
|
Sign up to set email alerts
|

Chemie der Ginkgolide, IV. Herstellung von Ginkgolid B aus Ginkgolid C

Abstract: Chemistry of Ginkgolides, IV1). – Synthesis of Ginkgolide B from Ginkgolide C The reaction of ginkgolide C (3) with tert‐butylchlorodiphenylsilane results exclusively in the formation of the 1‐O‐tert‐butyldiphenylsilyl ether 5, which when treated with O‐phenylchlorothioformate leads to the 7‐phenyloxythiocarbonyl derivative 6. The reduction of 6 with tributyltin hydride/AIBN yields the 1‐O‐tert‐butyldiphenylsilyl ether 7 of ginkgolide B (2). Removal of the silyl protective group with tetrabutylammonium fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…Although a selective silylation of 1-OH has been carried out by Weinges [40] the mechanism and scope of this reaction are not clear. We found that selective derivatization of 1-OH can be achieved by acyl migration from 6-O (iso-GC derivatives) via a six-membered cycle intermediate (Scheme 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Although a selective silylation of 1-OH has been carried out by Weinges [40] the mechanism and scope of this reaction are not clear. We found that selective derivatization of 1-OH can be achieved by acyl migration from 6-O (iso-GC derivatives) via a six-membered cycle intermediate (Scheme 3).…”
Section: Resultsmentioning
confidence: 98%
“…[35] However, acid-catalyzed esterification, [36] reaction of GC (3) with alkyl and aryl sulfonyl halides in the presence of pyridine [37,38] as well as silylation [39] takes place at 7-OH; a selective silylation at 1-OH in the presence of imidazole has also been described. [40] The use of solid-phase synthesis (SPS) for the preparation of ginkgolide derivatives appeared to be particularly attractive, as the presence of multiple hydroxyl groups provides several options for connecting points. Hence various strategies were investigated, including silicon, [41,42] sulfonyl, [43] Wang, [44,45] and Rink amide [46] linkers.…”
Section: Resultsmentioning
confidence: 99%
“…The four hydroxyl groups of ginkgolide C show highly different reactivities [Corey et al, 1992;Weinges and Schick, 1991;Weinges et al, 1993]. Apart from the tertiary hydroxyl group on C 3 , the 7-hydroxyl function is generally the least reactive of the three other groups.…”
Section: Chemistrymentioning
confidence: 98%
“…As a consequence of increased steric hindrance in its environment, the C 7 -hydroxyl group is the least reactive of the secondary hydroxyl groups of 1 [Corey et al, 1992;Weinges and Schick, 1991;Weinges et al, 1993]. However, selective oxidation or acetylation of the C 7 -hydroxyl group of 1 without protection of the other secondary hydroxyl groups have been reported [Corey et al, 1992;Jaracz et al, 2002].…”
Section: Chemistrymentioning
confidence: 96%